Pengaruh Strategi Promosi dan Harga Terhadap Keputusan Pembelian Pada Dealer Honda PT. Primadelta Starlestari Rangkasbitung - Eris Harismasakti; Didit Yadi Nugraha; Ade Jaya Sutisna (Universitas La Tansa Mashiro, 2022)
According to an initial survey conducted by researchers based on interviews with 15 prospective customers who were at Honda Dealers, that the promotions that had been carried out by Honda Dealers were deemed less emotionally interested in consumers, this was due to the lack of incessant promotions carried out by Honda Dealers. If the promotion is intense, consumers who were previously not interested in buying a product will become interested and try the product so that consumers make purchases from Honda dealers. To find out how big the influence of promotion strategies and prices on purchasing decisions at Honda dealers at PT. Primadelta Starlestari Rangkasbitung. This study involved a sample of 75 consumers at the Honda Dealer PT. Primadelta Starlestari Rangkasbitung. The data collection method is data processing. The data analysis method used is descriptive and hypothesis testing using regression analysis with SPSS 20.00 for windows program. It is known that the significance value for the simultaneous effect of X1 and X2 on Y is 0.004 and the calculated f value is 5.837 > from f table 3.12, so it can be concluded that H3 is accepted which means that there is an effect of X1 and X2 simultaneously affecting Y. In accordance with the research that has been done by the author Muchtar (2016)